(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
Field experiments were conducted in 2024–2025 to enhance the raw material (seed) yield of milk thistle (Silybum marianum L.) under Samarkand Province conditions. The study examined the effect of three different sowing dates on plant growth and seed yield. Results showed that the earliest sowing (mid-March) produced the highest raw material yield. Delayed sowing shortened plant development, significantly reducing seed yield. Analysis of two years of data supports early spring sowing as the optimal agro-technical practice for milk thistle cultivation in Samarkand, providing a foundation for improving its cultivation technology.